2004
DOI: 10.1212/01.wnl.0000103860.75218.a5
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake of fatty acids and fish in relation to cognitive performance at middle age

Abstract: Fatty fish and marine omega-3 PUFA consumption was associated with a reduced risk and intake of cholesterol and saturated fat with an increased risk of impaired cognitive function in this middle-aged population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
263
3
13

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 439 publications
(298 citation statements)
references
References 44 publications
15
263
3
13
Order By: Relevance
“…On the other hand, a trend towards a protective effect of n-6 PUFA against Alzheimer's disease was found in the CHAP study (66) , whereas no effect of n-6 PUFA on risk of dementia was seen in the Rotterdam Study (67) . Fish and seafood has a high content of long-chain n-3 fatty acids; in some although not all studies they have been positively associated with cognitive performance (64,(68)(69)(70)(71) . Such an association, however, was not seen in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a trend towards a protective effect of n-6 PUFA against Alzheimer's disease was found in the CHAP study (66) , whereas no effect of n-6 PUFA on risk of dementia was seen in the Rotterdam Study (67) . Fish and seafood has a high content of long-chain n-3 fatty acids; in some although not all studies they have been positively associated with cognitive performance (64,(68)(69)(70)(71) . Such an association, however, was not seen in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, four independent longitudinal studies have shown a significant relationship between regular fish consumption (at least weekly) and decreased risk of incident dementia (Kalmijn et al, 1997;Barberger-Gateau et al, 2002;Morris et al, 2003) or cognitive decline (Kalmijn et al, 2004). These results might be attributed to the long-chain omega-3 polyunsaturated fatty acids (n-3 PUFA) contained in fish oils, in particular docosahexaenoic acid (DHA), which is also a major component of the brain (Heude et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…DHA plays a relevant role in the preservation of both the histology and physiology of the neuronal tissue as the individual ages, by preserving the nervous system functions among which memory and learning are the most remarkable (Lukiw & Bazan, 2008). Several epidemiological studies have strongly established that a higher intake of foods rich in DHA (fatty fish and/or nutritional supplements based on fish oils or microalgae) is highly correlated with a lower risk of developing neurodegenerative diseases (Kalminj et al, 2004;Kalmijn et al, 1997), which is also associated with a clinical history indicating that patients with neurodegenerative disease have significantly lower levels of DHA in plasma and brain (Tully et al, 2003;Sodeberg et al, 1991).…”
Section: Dha and Brain Ageingmentioning
confidence: 99%
“…In neuronal tissue DHA is found in high concentrations, especially in the phospholipids of neuronal and glial membranes. However, as ageing progress and during the development of neurodegenerative diseases, a significant reduction in the DHA content of the brain is produced (Tully et al, 2003), especially in the cortex, cerebellum and hypothalamus, which result in a considerable reduction in the fluidity of neuronal membranes and an alteration of the neuronal homeostasis (Sodeberg et al, 1991;Kalminj et al, 2004). Beyond the effect of DHA at the neuronal membranes, the fatty acid also exerts other protective effects which are mediated by a metabolic derivative named neuroprotectin D-1 (NPD-1) which may protect neurons against oxidative stress, inflammation, disruption of the cytoskeleton and from the activation of apoptotic signaling pathways (Bazan, 2009).…”
Section: Introductionmentioning
confidence: 99%